2016
DOI: 10.5897/ajb2015.15043
|View full text |Cite
|
Sign up to set email alerts
|

Asymbiotic seed germination and in vitro propagation of Brasiliorchis picta

Abstract: Seed storage method for in vitro germination and propagation from leaves of Brasiliorchis picta was developed. Seeds were harvested and stored at-20 and-80°C for 1, 3, 6, and 12 months and were germinated on Knudson C (KC), Murashige and Skoog (MS), half-strength MS (½ MS macro-and micronutrients), and woody plant medium (WPM). Seeds stored at-20°C, the recommended temperature for seed banks, had a high germination rate (76.0%) when cultivated in WPM after 12 months of storage. WPM is the best medium for seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Mahendran et al [27] reported a higher percentage of germination in epiphytic orchids Cymbidium bicolor on LO medium than KCM, KC, and MS media. Pradhan et al [28] reported that MS was the most suitable for germination of Cymbidium aloifolium rather than KC, PM, and VW media, whereas dos Santos et al [29] working with Brasiliorchis picta , an epiphytic orchid, found WPM to be significantly higher than KC, 1/2 MS, and MS media. Roy et al [30] claimed that Phytamax medium was the most suitable for germination and protocorm development of Vanda coerulea than Vacin and Went, MS, and Knudson C media.…”
Section: Resultsmentioning
confidence: 99%
“…Mahendran et al [27] reported a higher percentage of germination in epiphytic orchids Cymbidium bicolor on LO medium than KCM, KC, and MS media. Pradhan et al [28] reported that MS was the most suitable for germination of Cymbidium aloifolium rather than KC, PM, and VW media, whereas dos Santos et al [29] working with Brasiliorchis picta , an epiphytic orchid, found WPM to be significantly higher than KC, 1/2 MS, and MS media. Roy et al [30] claimed that Phytamax medium was the most suitable for germination and protocorm development of Vanda coerulea than Vacin and Went, MS, and Knudson C media.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to symbiotic cultivation of D. bigibbum with the selected Basidiomycota, matured seeds were grown in Modified Knudson C orchids medium, and the different stages of germination based on the study of Yamazaki and Miyoshi (2006) In previous studies of Hynson et al (2013) and Santos et al (2016), it was observed that during seed germination of several species of orchids, such as Dendrobium, imbibition of water, embryo expansion, and rupture of testa occurred through in vitro culture without any fungal symbiont. This happened when the mature and viable seeds absorb water from the medium and the growth continues in the presence of exogenous carbon supply.…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al (2016), obtained a high survival percentage using vermiculite as substrate. Conversely, is convenient to use substrates of easy availability and of low costs to optimize the production.…”
Section: Discussionmentioning
confidence: 99%